Gereja Mula-Mula sebagai Permodelan Komunitas bagi Pemuridan Gereja Masa Kini - Sugito, Yehudha Andrew (JURNAL TERUNA BHAKTI, 2023)
The Central Bureau of Statistics provides a projection of the explosion of the productive age population (15-64 years old) exceeding the non-productive age population from 2020 to 2030. This projection should encourage the Church to strategize for the growth of the Church, especially for the productive-aged youth. On the other hand, the level of congregational involvement in discipleship is closely related to the growth of the Church in quantity. Regarding quality, the church's most important aspect of the ministry to young people is to deepen their spirituality by forming solid communities. These projections illustrate that discipleship through community becomes a model for strategizing church growth. This model also became the model of discipleship in the early church. Through a literature study, this research examines the challenges facing discipleship in the Church today. In addition, this research also investigates the community model in the early Church, which covers three areas, namely the foundation and purpose of the community, the depth of participation (engagement) in the community, and the formation of identity in the community. The results of this research on the community model in the early Church turned out to have significant implications for the preparation of the discipleship model in the Church today, as well as being an answer to the challenges of discipleship in the Church today. Abstrak Badan Pusat Statistik memberikan proyeksi meledaknya jumlah penduduk yang berusia produktif (15-64 tahun) melebihi penduduk yang berusia tidak produktif, pada kisaran tahun 2020 hingga 2030. Proyeksi ini seharusnya mendorong gereja untuk menyusun strategi bagi pertumbuhan gereja terutama bagi generasi muda yang berusia produktif. Di sisi lain, tingkat keterlibatan jemaat dalam pemuridan, ternyata erat kaitannya dengan pertumbuhan gereja secara kuantitas. Secara kualitas, aspek terpenting dari pelayanan yang ditawarkan gereja kepada kaum muda untuk memperdalam spiritualitas mereka adalah melalui terbentuknya komunitas yang kuat. Proyeksi-proyeksi ini memberikan gambaran bahwa pemuridan melalui komunitas menjadi model dalam menyusun strategi pertumbuhan gereja. Model ini ternyata juga menjadi model pemuridan di gereja mula-mula. Melalui studi kepustakaan, penelitian ini meneliti tentang tantangan yang dihadapi pemuridan di gereja masa kini. Selain itu penelitian ini juga meneliti tentang model komunitas di gereja awal yang meliput tiga area, yakni landasan dan tujuan komunitas, kedalaman partisipasi (engagement) dalam komunitas dan pembentukan identitas dalam komunitas. Hasil penelitian tentang model komunitas di gereja awal ini ternyata memiliki implikasi yang besar bagi penyusunan model pemuridan di gereja masa kini serta menjadi jawaban bagi tantangan-tantangan pemuridan di gereja masa kini.